2002
DOI: 10.1557/jmr.2002.0095
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Phase Transition in Epitaxial BaTiO3 Thin Films

Abstract: The thickness dependence of the dielectric properties of epitaxial BaTiO3 thin films was investigated for thicknesses ranging from 15 to 320 nm. The films were deposited by low-pressure metalorganic chemical vapor deposition on (100) MgO substrates. The relative dielectric permittivity and the loss tangent values decreased with decreasing thickness. High-temperature dielectric measurements showed that with decreasing film thickness, the ferroelectric-to-paraelectric transition temperature decreased, the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 20 publications
6
16
0
Order By: Relevance
“…As the sputtering is proceed in an oxygen deficient atmosphere, thus the oxygen vacancies induced structural disorders and compositional fluctuations in the film may be responsible for the observed relaxor behavior. Similar diffusive transition had also been observed in BTO films on MgO and Pt-coated Si substrates [94,95].…”
Section: Phase Transitionsupporting
confidence: 77%
“…As the sputtering is proceed in an oxygen deficient atmosphere, thus the oxygen vacancies induced structural disorders and compositional fluctuations in the film may be responsible for the observed relaxor behavior. Similar diffusive transition had also been observed in BTO films on MgO and Pt-coated Si substrates [94,95].…”
Section: Phase Transitionsupporting
confidence: 77%
“…The large domain gradient for relatively modest strains is due to the weak tetragonality of BaTiO 3 . The strain/domain gradient through the film thickness could help explain the broad phase transitions and relaxor-like behavior often observed in epitaxial thin films [3].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gopalan and Raj [2] have demonstrated that the measured second-harmonic generation coefficient depended on the volume fraction of each domain type. The strain state of the film can also affect the Curie transition temperature and induce relaxor-type behavior [3]. Furthermore, Hoerman et al [4] have shown that the dynamics of the electro-optic response in polydomain films are dependent on domain structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, together with the experimental data. It has to be noted that the calculated values along the whole range 32 an increase of permittivity with the thickness of the film has been observed in the whole range of temperature. Such an increase has been related to a stress relaxation as the film became thicker.…”
mentioning
confidence: 83%